A Battle for Hearts and Minds: Turenne and Louis XIV. (June 2014) - Stone, Harriet
<x content-type="archive" xml:space="preserve">Abstract</x> A commemorative fan marking the death of Turenne in 1675 is striking for its presentation of the general's dead body. In addition to the fan, I consider Turenne as eulogized by Fléchier, along with depictions of the death of Louis XIV by Dangeau, Saint-Simon, and in the official autopsy report. The experience of death disrupts the classical ideal. Playing out tensions between the body, the mind, and the soul, representations of death complicate Descartes's binarism and, in particular, the philosopher's concept of the mechanical body.